OPTIMALISASI PENGOLAHAN SAMPAH RUMAH TANGGA MELALUI PEMBUATAN PUPUK KOMPOS DI DESA PENGADANGAN, KECAMATAN PRINGGASELA, KABUPATEN LOMBOK TIMUR - Askit, Baiq Ratna; Fauziana, Syabina Laila (Jurnal Wicara, 2024)
Kuliah Kerja Nyata (KKN) program is a form of community service by students as part of the education curriculum in Indonesia. KKN activities in Pengadangan Village, Pringgasela District, East Lombok Regency, focus on optimizing household waste processing through making compost. This program aims to utilize the agricultural potential in the village, as well as provide solutions to the problem of household waste that has not been managed properly. The main activities carried out include socialization and training in making compost using the biopore method. The results of this activity are expected to support sustainable green economy programs and increase public awareness of the importance of environmentally friendly waste management.